"I just want to live" : an interpretative phenomenological analysis of separation abuse in South African heterosexual relationships - Johnson, Samantha-Sue (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
A key strategy for ending IPV, would be to make it possible for potential victims to safely leave their abusers. However, the abuse may persist, often with devastating consequences. The current literature on separation a buse primarily makes use of quantitative research to explain the phenomenon as is visible in the large amounts of quantitative research that was cit ed throughout this research project. Therefore, the aim of this research was to qualitatively explore the lived experiences of South African women who had experienced separation a buse . The Power and Control Wheel, located within Feminis t Theory, was used as the theoretical framework as it offers an illustrative understanding of the types of abuse that exists within a relationship and was adjusted to suit post - separation a buse . The research was conducted in Makhanda (formerly known as Grah amstown ) , Eastern Cape with the assistance of the local Families South Africa (FAMSA) office. Four participants were interviewed using an Interpretative Phenomenological Analysis (IPA) approach. IPA was chosen as it involves a detailed exploration of how p articipants make sense of their personal and social worlds as well as determining the meanings that participants relate to their personal experiences and events in their lives. Data was collected through semi - structured interviews which were conducted by t he researcher with the assistance of a translator for the participants who preferred to speak Isi - Xhosa. Each participant initially participated in a screening interview conducted by a FAMSA staff member before being interviewed to minimize harm that could be caused through speaking about their experience before they were ready. The interviews were analysed through the use of IPA techniques where themes were extracted from the data. Five superordinate themes emerged from the analysis, namely "types of abuse experienced post-separation" , "children and abusive relationships" , "drinking and substance SEPARATION ABUSE IN SOUTH AFRICA ii abuse" , "protection order" and "hope for the future" . The findings revealed the ways in which the abusers continued their abuse during the separation period, the participant's experiences of separation abuse as well as the experiences they believed their children had throughout the process. Two of the participant's also revealed they feared for their lives, which resulted in them applying for protection orders. Despite the years of abuse suffered at the hands of their ex -partners, all four participants remained hopeful that they could become independent enough to provide for their children and themselves. While there have been South African studies which look at stalking victimization, the IPV female mortality rate and power and powerlessness experienced by women leaving abusive relationships, there is currently no published study in South Africa that explicitly focuses on separation abuse in heterosexual relationships in South Africa. Therefore, it was be neficial to conduct this research as the need exists to conduct research that not only focuses on the homicide rates of females at the hands of their partners but also the types of separation abuse that exists.
Keywords: Phenomenological psychology; Family violence -- South Africa -- Case studies; Women -- Violence against -- South Africa -- Case studies; Intimate partner violence -- South Africa -- Case studies